Bibliometric analysis of 50 years of IEEE Industrial Electronics Society publications - Fernandes, João M. (2018)
Tertiary education increasingly relies on publications. Arguably, Ph.D.\@ work is also increasingly produced within larger teams or with more extensive collaborations. As way to obtain an objective measure of this trend, this manuscript examines authorship trends in IEEE Industrial Electronics Society (IEEE-IES) publications for the 50-year period from 1963 to 2012. We emphasize the trends related to the number of authors and pages per publication. In order to identify several bibliometric indicators, we have analyzed 34,409 entries from IEEE-Xplore digital library for IEEE-IES publications. We provide results for two different sets of publications. Firstly, we present evidence that the number of authors and the number of pages of articles in the IEEE Transactions in Industrial Electronics (TIE) for the 50-year period are increasing per decade an average of +0.42 authors and +0.87 pages, respectively. Secondly, we provide evidence that the number of authors per article in 14 publication venues for the 25-year period from 1988 to 2012 are increasing per decade an average of +0.375 authors.